Assessing the impact of gender and body mass index on motor competence: a cross-sectional analysis of children - Sandeep Kumar; Yajuvendra Singh Rajpoot; Krishna Kant Sahu; Bhanu Pratap; Suchishrava Choudhary; Prashant Kumar Choudhary; Nripender Hooda (Pedagogy of Physical Culture and Sports, 2025)
Background and Study Aim. Fundamental motor skills in children serve as the basis for constructing more complex movement patterns. Therefore, the quality of mastering these skills, relative to children's age, largely determines success. These skills are influenced by both gender and weight status. This study aimed to analyze gender differences and the relationship between BMI and motor competence in school-aged children.